2020
DOI: 10.1088/1757-899x/973/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Passive vibration damping of a cantilever plate

Abstract: Vibration control of mechanical systems divided into two types active and passive, this case study illustrates other approach of passive control of the cantilever plate by using double layers of the viscoelastic material (Dyad 606) one in the upper face of the Al substrate (5051) and the second one in the lower face. This layers are affected by axial uniform distributed force by applying tension load, the damping level depend on the value of this axial force where the vertical component of this force consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The values of the interaction parameters for all viscous drag process are given elsewhere . The prediction of the above criterion (the original and the modified) for a transition in creep behavior from viscous drag control to climb control with decreasing normalized stress was shown to agree very well with the behavior of many solid‐solution alloys (Figure b,c).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The values of the interaction parameters for all viscous drag process are given elsewhere . The prediction of the above criterion (the original and the modified) for a transition in creep behavior from viscous drag control to climb control with decreasing normalized stress was shown to agree very well with the behavior of many solid‐solution alloys (Figure b,c).…”
Section: Discussionmentioning
confidence: 60%
“…The prediction of the above criterion (the original and the modified) for a transition in creep behavior from viscous drag control to climb control with decreasing normalized stress was shown to agree very well with the behavior of many solid‐solution alloys (Figure b,c). For example, it was demonstrated that the creep behavior of Al–Zn alloys, Al–Ag alloys, and Ni–Fe alloy (see the study by Mohamed for the data and the plots) was consistent with the modified criterion, as expressed by Equation .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations